The Effectiveness of Nutrition Counseling on The First Thousand Days of Life Group in Improving Knowledge and Attitude on Nutrition Awareness - Ancah Caesarina Novi Marchianti; Elly Nurus Sakinah; Nurud Diniyah (Journal of Agromedicine and Medical Sciences, 2017)
Nutrition status in the first thousand days of life (FTDL) of 270 days during pregnancy and 730 days in the infant's first life is a critical period, since the resulting consequences are permanent and irreparable. There are still many problems in the group of FTDL around the campus of University of Jember which require intensive handling, such as stunting, low energy protein, anemia, underweight and etc. Methods of improving the quality of nutrition for the FTDL group can be done by increasing knowledge about nutrition through counseling by utilizing various media (posters, brochures, videos, demos and presentation slides). This study aims to determine how far is the effectiveness of nutrition counseling in improving knowledge and attitude awareness on nutrition problems. The method used was to give counselling on nutrition in the target groups (members of Posyandu Catleya A and B) and assessed changes by comparing the level of nutritional knowledge and attitude before and after receiving counseling. The results showed there were significant differences in the level of nutritional knowledge and attitude between before and after the counseling about nutrition and food processing technology. It can be concluded that this method is quite effective to raise awareness of FTDL group on nutrition problems. Keywords: food insecurity, nutrition counseling, nutrition awareness